Personality Determinants of Attitudes Toward Seeking Mental Health Services - De Leon, Camille V.; Sanchez, Maria Zharina (Philanthropy: Journal of Psychology, 2025)
Mental health service utilization in the Philippines remains low despite significant psychological distress and recent legislative reforms aimed at improving access. Understanding factors influencing help-seeking attitudes is crucial for addressing this disparity. This study investigated the personality determinants of attitudes toward seeking mental health services. A cross-sectional design was employed with a sample of 294 Filipino adults, and data were analyzed using correlation analysis. Results indicated that Conscientiousness and Extraversion were significantly and positively correlated with psychological openness (r=.155, p< .01) and help-seeking propensity (r=.128, p< .05); while Neuroticism was negatively associated with the attitudes of psychological openness (r =-.209, p < .01) and indifference to stigma (r = -.128, p< .05) and showed Conscientiousness positively correlates with stigma sensitivity (r=.131, p < .05). These findings suggest that certain personality traits can either facilitate or hinder an individual's willingness to seek professional psychological help, highlighting the need for tailored interventions that consider internal personality factors in promoting mental health service utilization.